(untitled) (Research, Society and Development, 2021)
This article objective report the experience of students of nursing as monitors in a laboratory practice nursing of a community university. It is na report experience, realized with students nursing, relative to the actions developed a from March 2018 to October 2020, through the monitoring of the nursing practices laboratory, which is linked to the undergraduate nursing course of a Community University. The experiences are based on four pillars: the constant needto revise the theory to associate it with practical activities; the improvement of interpersonal communication between the triad monitor-student-teacher; the practical development of exercise ethical professional; and approximation of management of the laboratory with the practice management in nursing. The actions provided the potentialization of formation of critical-reflective, the share of experiences in construction of the teaching-learning process and the enhancement of the technical-practical-scientific abilityof the students.